THE INFLUENCE OF FINANCIAL KNOWLEDGE, FINANCIAL ATTITUDES AND PERSONALITY TO FINANCIAL MANAGEMENT BEHAVIOR FOR MICRO, SMALL AND MEDIUM ENTERPRISES TYPICAL FOOD OF COTO MAKASSAR - Budiandriani .; Khairina Rosyadah (JHSS (JOURNAL OF HUMANITIES AND SOCIAL STUDIES), 2020)
This study aims to analyze the effect of financial knowledge, financial attitudes, and personality on financial management behavior in micro, small, and medium-sized businesses of the typical Coto Makassar food in Makassar. This research is included in the causal associative research. The subjects of this study were all owners of micro, small, and medium enterprises of Coto Makassar typical food totaling 63 units, and as many as 32 units as a sample. Data were analyzed using multiple linear regression using the SPSS version 21 program. The data collection technique used a questionnaire. The results showed that (1) financial knowledge has a positive and significant effect on financial management behavior; (2) financial attitudes have a positive and significant effect on financial management behavior; and (3) personality has a positive and significant effect on financial management behavior